Corporate Social Responsibility in Afghanistan: A Critical Case Study of the Mobile Telecommunications Industry - Sameer Azizi (Copenhagen Business School (CBS), 2017)
This doctoral dissertation examines the business-development relations in Afghanistan by focusing on Corporate Social Responsibility (CSR) and other related practices from corporations in the Afghan mobile telecommunications industry. More concretely, the study aims to explore the characteristics and drivers of the various CSR practices in the Afghan mobile telecommunications industry in order to critically assess the relationship between CSR and development in such context. The thesis highlights that the national context of Afghanistan in combination with the global mobile telecommunications industry provides a relevant empirical focus that can enrich the theoretical debates about CSR in developing countries. The study thereby stresses on the importance of context, and integrates both the societal and corporate dimensions to study CSR by corporations in the Afghan mobile telecommunications industry. The study draws from the political governance literature on `Areas of Limited Statehood' (ALS) to conceptualize the national context of Afghanistan, and to problematize the assumptions and claims of the CSR literature by focusing particularly on the neo-institutional, the political and the developmentoriented debates on CSR. The empirical data for the study is based on an intensive case study of four large and foreignowned mobile telecommunications operators in Afghanistan. The case study includes qualitative data from various sources including interviews and observations during fieldwork in Afghanistan, and a study of secondary data from the corporations, Afghan state institutions, civil society and other relevant actors.
hdl:10398/9466
Keywords: 650